Chemistry of Stable Carbenes and «Green» Technologies - Korotkikh, N.I.; Saberov, V.Sh.; Rayenko, G.F.; Glinyana, N.V.; Knishevitsky, А.V.; Shvaika, О.P. (Science and Innovation, 2024)
The fundamental researches in the chemistry of stable carbenes carried out by the Litvinenko Institute of Physical, Organic & Coal Chemistry of NAS of Ukraine (IPOCC) over the last decade and applications in the field of «green» technologies based on the results of these researches have been described. Carbene versions of Claisen ester condensation with the formation of zwitterionic compounds, the Leuckart-Wallach reaction with the autoreduction of carbenoid azolium salts, the Hofmann cleavage of aminocarbene insertion products, induced tandem autotransformation of 1,2,4-triazol-5-ylidenes into 5-amidino-1,2,4-triazoles have been discovered. New carbene reactions of addition, deesterification, oxidation, and complex formation have been found. Effective methods for obtaining stable carbenes and carbenoids have been suggested. New types of carbenes, benzimidazolylidenes, superstable conjugated bis-carbenes, and carbenoids have been synthesized. The existence of hypernucleophilic carbenes has been theoretically predicted and experimentally confirmed. Prospects for the use of carbenes and their derivatives, in particular, carbene complexes of transition metals in the catalysis of organic reactions and the search of biologically active compounds have been outlined.